COMPETENCE OF LATVIAN PRESCHOOL TEACHERS TO INCLUDE NEWCOMERS IN EDUCATION - Tarune, Iluta; Usca, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The 21st century is the time of globalization, and migration has become the norm. As a result of these trends, the education systems must be inclusive in order to ensure the right of all children to education, regardless of their background. Preschool teachers play an essential role in the implementation of inclusive education. They have the opportunity and tools to form a foundation for further education by creating a positive and supportive environment where all children can feel welcome. In order to promote inclusion, preschool teachers must have certain competences for the inclusion of newcomers in education. The paper presents a structural model of preschool teacher competence for the inclusion of newcomers in education and the results of the preschool teacher questionnaire. The research results show that Latvian preschool teachers' competence to work with newcomer children is insufficient and needs to be improved.